Evaluasi Area Kawasan Keselamatan Operasi Penerbangan (KKOP) Akibat Perubahan Panjang Runway (Studi Kasus : Bandar Udara Internasional Sultan Syarif Kasim II Pekanbaru) - Nur Ihsan; Ari Sandhyavitri; Sri Djuniati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The objective of the study was to evaluate and to calculate the required the existing 2016 and ultimate 2035 KKOP of Sultan Syarif Kasim II International Airport Pekanbaru. The KKOP area was drawn using ArcGIS Software package, the calculation was carried by using ICAO Manual Standard Annex 14 2013, Ministry Decree Number 60 2004 and Number 3 2016. It is identified that Approach and Take Off Surface in 2016 = 155 meters AES and in 2035 = 152 meters AES, the elevation for inner horizontal surface in 2016 = 50 meters AES and in 2035 = 47 meters AES , the discreapancy for both approach surface elevation of 1,97% to 6,38% for inner horizontal surface. It is also identified that runway length in 2016 = 2.600 meters will be extended to 3.000 meters in 2035, than area of inner horizontal in 2016 = 34.783.800 m2 became in 2035 = 50.300.000 m2, it’s not necessary the change of runway length from 2016 to 2035 affected to unincreased in KKOP elevation usualless KKOP distance length.Key Word: Sultan Syarif Kasim II International Airport, Obstacle Limitation Surface, AES